Altered Variability and Concordance of Dynamic Resting-State Functional Magnetic Resonance Imaging Indices in Patients With Major Depressive Disorder and Childhood Trauma - Luo, Qianyi; Yu, Huiwen; Chen, Juran; Lin, Xinyi; Wu, Zhiyao; Yao, Jiazheng; Li, Yuhong; Wu, Huawang; Peng, Hongjun (Frontiers in Neuroscience, 2022)
Childhood trauma is a non-specific risk factor for major depressive disorder (MDD). Resting-state functional magnetic resonance imaging (R-fMRI) studies have demonstrated changes in regional brain activity in MDD patients who experienced childhood trauma. However, previous studies have mainly focused on static characteristics of regional brain activity. This study aimed to determine the specific brain regions associated with MDD with childhood trauma by performing temporal dynamic analysis of R-fMRI data in three groups of patients: MDD patients with childhood trauma (n = 48), MDD patients without childhood trauma (n = 30), and healthy controls (n = 103). Dynamics and concordance of R-fMRI indices were calculated and analyzed. In MDD patients with childhood trauma, a lower dynamic amplitude of low-frequency fluctuations was found in the left lingual gyrus, whereas a lower dynamics degree centrality was observed in the right lingual gyrus and right calcarine cortex. MDD patients with childhood trauma showed a lower voxel-wise concordance in the left middle temporal and bilateral calcarine cortices. Moreover, group difference (depressed or not) significantly moderated the relationship between voxel-wise concordance in the right calcarine cortex and childhood trauma history. Overall, MDD patients with a history of childhood trauma demonstrated aberrant variability and concordance in intrinsic brain activity. These aberrances may be an underlying neurobiological mechanism that explains MDD from the perspective of temporal dynamics.